The impact of the EU General Data Protection Regulation on innovation in firms - Knut Blind; Crispin Miles Niebel; Christian Rammer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
In May 2018, a new regulation by the European Commission on data protection came into force, the General Data Protection Regulation (GDPR). It requires many firms to update their data protection strategy. It may also complicate different types of data usage, particularly related to data on individuals. In the literature, there is little evidence and no consensus on whether this new privacy regulation is beneficial or detrimental to innovation. This study provides empirical evidence on the impact of the GDPR on innovation activities in firms. Exploiting panel data from the German innovation survey, a difference-in-difference analysis shows that the GDPR stimulated additional innovation activity while shifting the focus of innovation away from radical and towards more incremental innovation. This holds for both firms that report that the GDPR complicated their innovation efforts, and for the much smaller group of firms that report that the GDPR facilitated their innovation activities. Finally, larger and older firms experience higher increases in their turnover with incremental innovation compared to smaller and younger firms.
Keywords: O31; O38; C22; L51; 330; General Data Protection Regulation; Innovation; Community Innovation Survey; Difference-in-difference estimation